Potential changes in the competitiveness of maize growers in Central Chile through the use of transgenic seed (Bt and RR) - Diaz Osorio, J.; Herrera, R.; Valderrama, J.; Llanos Ascencio, J. L. (Spanish Journal of Agricultural Research, 2004)
A number of studies have shown that the use of transgenic seed increases productivity, reduces the quantities of pesticide required to protect crops, and cuts down the labour involved in cultivation. Besides saving time, this reduces manpower requirements and the use of farm machinery, and the use of such seed has had an important economic (and environmental) impact on the production of certain crops. These advantages translate into reduced production costs-particularly so for a number of crops whose international market price has fallen steadily over the last ten years. Current Chilean legislation, however, only allows the multiplication of genetically modified plants whose final product is destined for export. The aim of this work was to compare the production costs associated with conventional and transgenic Bt and RR maize, and therefore to highlight the potential economic benefits to Chile of opening the market to genetically modified seed.